2020
DOI: 10.18203/2349-2902.isj20203506
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of efficacy between 0.2% of topical glyceryl trinitrate and lateral anal sphincterotomy

Abstract: Background: Anal fissure is a linear tear in the lining of the anal canal below the dentate line. Among the conservative modalities glyceryl trinitrate (GTN) is emerging as first line of treatment since it breaks the vicious cycle and relaxes the sphincter. Surgery was considered as the first line of treatment if conservative measures such as bulk laxatives, stool softeners and local anaesthetics fail. Aim of this study was to study the aetiology and predisposing factors, age and sex distribution, clinical pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Half of the patients with anterior fissures have a history going back to birth. Acrochordon was detected in 82.69% of men and 81.81% of women, which has been observed in various Treatment Failure Men Women studies as a common occurrence in fissures [16][17] . A variety of treatment options are available for chronic anal fissures, ranging from simple dietary adjustments, laxatives, topical application of GTN, Ca channel blockers, to more invasive surgical interventions such as lateral internal sphincterotomy [18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Half of the patients with anterior fissures have a history going back to birth. Acrochordon was detected in 82.69% of men and 81.81% of women, which has been observed in various Treatment Failure Men Women studies as a common occurrence in fissures [16][17] . A variety of treatment options are available for chronic anal fissures, ranging from simple dietary adjustments, laxatives, topical application of GTN, Ca channel blockers, to more invasive surgical interventions such as lateral internal sphincterotomy [18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…18 also reported that not only higher healing rates of chronic anal fissure were achieved by treatment through "lateral internal sphincterotomy (LIS)", the difference in the healing rates from the use of "topical GTN ointment" was also statistically significant [85% vs 74%; (p = 0.0001). Also, Paul et al 19 also found that "LIS" provided much higher healing rates as compared to "GTN" (86.8% and 66.6%, respectively). In terms of recurrence, two patients in the "GTN" group had recurrence while none in "LIS" group had recurrence during study period.…”
Section: Mean Agementioning
confidence: 94%